Effective General Practice–Led Interventions to Increase Uptake in Colorectal Cancer Screening: A Scoping Review. - Kelly, Anna M.; Walker, Stephanie C.; Carney, Georgia; Levu, Kelera; Horn, Christopher; Jenkins, Mark A.; Taylor, Natalie; Feletto, Eleonora (Journal of Public Health Management & Practice)
Supplemental Digital Content is Available in the Text. Context: Primary care, specifically general practice, represents the front line of health care. For colorectal cancer (CRC) screening, general practice provides an effective setting to improve participation in organized screening. Objective: The aim of this study was to review evidence from systematic reviews with meta-analyses (SRMAs) on interventions to increase CRC screening, and from randomized controlled trials (RCTs) on the effectiveness and implementation of general practice–led interventions. Design: This scoping review included 2 phases: 1) an umbrella review of SRMAs evaluating CRC screening participation after intervention delivery, and 2) a review of RCTs evaluating general practice–led interventions, which were also coded for implementation strategies. Eligibility Criteria: For the SRMAs, interventions could be designed to increase participation of any type of population-based CRC screening. For the RCTs, only general practice–led interventions designed to increase screening using fecal occult blood tests were included. Studies had to be published in English and available in full text. Study Selection: We searched MEDLINE, Embase, and PsycInfo, guided by PRISMA guidelines, from May 2016 to August 2023. Main Outcome Measure(s): All evidence was assessed for intervention effectiveness and, for RCTs, implementation strategies using one implementation science framework and 2 taxonomies. Results: We identified 15 SRMAs and 12 RCTs, which evaluated individual, primary care/general practice, and population-level interventions. Key interventions including patient reminders, risk assessment tools, and kit outreach improved CRC screening participation. Evidence on multicomponent interventions is promising. None of the included RCTs explicitly outlined implementation strategies. Conclusions: Our findings highlight the possible effectiveness of individual, primary care/general practice, and population-level interventions and their potential use in combination. However, there was a lack of implementation strategies to support adaptation and sustainability. Future trials should explore how interventions can mobilize general practice to promote CRC screening, incorporating targeted implementation strategies to enhance their real-world application and sustainability.